TO REVIVE AN ABUNDANT LIFE: Catholic Science and Neoextractivist Politics in Peru's Mantaro Valley. (February 2017) - GRAETER, STEFANIE
ABSTRACT: Since the turn of the twenty‐first century, the rapid growth of Peru's extractive industries has unleashed diverse forms of political resistance to an economic system dependent on ecological destruction and human harm. In the central highlands of Peru, a Catholic scientific project based out of the Archdiocese of Huancayo undertook six years of research on heavy‐metal contamination in the Mantaro Valley. This included lead‐exposure studies in the notoriously polluted city of La Oroya, home to the country's largest polymetallic smelter. How did the Catholic Church become an apt institution for the production of science in this region? Drawing on fieldwork with the Revive the Mantaro Project, this article conceptualizes the integration of religious and scientific practitioners and practices and the political landscape that necessitated, shaped, and limited them. Technocratic governance and anti‐leftist sentiments made science a suitable political idiom for the Catholic Church to enact its ethos of abundance and demand the legitimacy of life beyond bare life. A state of endemic corruption and epistemic mistrust also obliged Catholic accompaniment to scientific practices to generate trust for the researchers and to provide ethical credibility as their knowledge entered the fray of national mining politics. Ultimately contending with entrenched systems of power, the Revive the Mantaro Project's significance extended beyond political efficacy; its practices enacted a world of democracy, rights, and legal protections not yet of this world.